2015
DOI: 10.1111/jpc.12980
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycaemic hyperosmolar syndrome in children: Patient characteristics, diagnostic delays and associated complications

Abstract: Characteristics of children with HSS are variable for age, gender and BMI-for-age percentile and not predominately limited to obese male adolescent African-American. Delay in diagnosis is common and morbidity and mortality in paediatric HHS are significant. The subsequent diagnosis of patients presenting with HHS includes type 1 and 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 17 publications
2
36
0
Order By: Relevance
“…Rhabdomyolysis is a possible cause of the diminishing renal function complication in this case that was effectively reversed by temporary Hemodialysis. clinical case reaffirms the possibility of developing DKA with some manifestations of HHS in adolescent in the context of unknown T2D, which only few have been recognised and reported [5,6].…”
Section: Discussionsupporting
confidence: 69%
“…Rhabdomyolysis is a possible cause of the diminishing renal function complication in this case that was effectively reversed by temporary Hemodialysis. clinical case reaffirms the possibility of developing DKA with some manifestations of HHS in adolescent in the context of unknown T2D, which only few have been recognised and reported [5,6].…”
Section: Discussionsupporting
confidence: 69%
“…Undiagnosed diabetes mellitus, most often type 2, with underlying infection is the most common cause of HHS, as it was in the presented case [1]. It is, however, still an unusual presentation of type 2 diabetes in children, found in 2% of cases, developing due to diagnosis delay, which also occurred in our patient [3][4][5]. Recent studies showed an increase of HHS prevalence in the paediatric population [6,7]; it is therefore important to know how to diagnose and treat this condition.…”
Section: Discussionsupporting
confidence: 48%
“…It is believed to be associated with a delay in the diagnosis of these diseases. Mortality in the course of HHS reaches 20-30%, and it is approximately 10-times higher than in diabetic ketoacidosis (DKA) [3,4].…”
mentioning
confidence: 99%
“…However, untreated HHS leads to death [1]. Mortality ranges from 5 to 20%, which is about 10 times higher compared with DKA, due to higher age or delayed diagnosis [4][5][6]. Previous studies reported higher occurrence of HHS in females and older patients (60 + years) and at diabetes onset [7][8][9].…”
Section: Introductionmentioning
confidence: 99%